2003
DOI: 10.1063/1.1589194
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting photoluminescence in freestanding GaN templates

Abstract: We studied time-resolved photoluminescence (PL) over a temporal range 10−6–103 s in high-purity freestanding GaN templates. Red, yellow, green, blue, and shallow donor–acceptor emission bands can be resolved in the PL spectrum. Observation of luminescence long after the excitation is switched off is a striking feature of our study. The persistent PL observed for all above bands, except for the green band, is primarily attributed to the donor–acceptor-pair-type recombination. An unusually slow, nonexponential d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…The GL band (maximum at about 2.45 eV) rapidly transforms into the YL band (2.2 eV) after about 10 À4 s following the excitation pulse. The non-exponential decays of PL at 15 K have been attributed to the donor-acceptor-pair (DAP) transitions involving a shallow donor and different acceptors, whereas the transformation of the GL into YL has been attributed to the manifestation of two charge states of the same acceptor, presumably V Ga O N complex [3].…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The GL band (maximum at about 2.45 eV) rapidly transforms into the YL band (2.2 eV) after about 10 À4 s following the excitation pulse. The non-exponential decays of PL at 15 K have been attributed to the donor-acceptor-pair (DAP) transitions involving a shallow donor and different acceptors, whereas the transformation of the GL into YL has been attributed to the manifestation of two charge states of the same acceptor, presumably V Ga O N complex [3].…”
Section: Methodsmentioning
confidence: 98%
“…Previously, we proposed that the dominant defect responsible for the yellow (YL) and green luminescence (GL) bands in freestanding GaN templates is a deep acceptor, presumably a gallium vacancy-oxygen complex (V Ga O N ) in the 0/À and À/2À charge states [2]. Time-resolved PL (TR-PL) study at low temperatures revealed a transformation of the GL band into the YL band and very slow non-exponential decay of the latter [3]. In the present work, we have studied the effect of temperature on the TR-PL in the freestanding GaN.…”
Section: Introductionmentioning
confidence: 99%
“…Сarriers captured in QW reveal long-lived kinetics in microsecond scale [5]. Moreover PL signal from electron hole pair could be clearly detected up to tens of second after excitation due to non-exponential decay of carrier concentration [6,7]. Bleaching effect could be reduced by lowering of Al percentage in Al Ga 1− As QW barriers down to few percent [8].…”
Section: Introductionmentioning
confidence: 80%
“…Indeed, the Si doping has been found to be able to suppress the formation of point defects in GaN and prevent from the potential irregularities at the domain boundaries in Si doped layers [21]. Thus, we point out that the defects near the surface play an important role in emission mechanisms in GaN thin films [11] and are responsible for the inefficient band-edge emission observed in the PL spectra.…”
mentioning
confidence: 92%
“…It was found that the effect of surface layer is closely related to the optical properties of GaN upon annealing [8] or after surface treatment [9,10]. Besides, the existence of the surface state has been considered as the possible reason for the observation of persistent photoluminescence (PL) in GaN [11]. Recently, there have been several reports concerning the electric force microscopy (EFM) on GaN samples [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%